Cerealusog cereal milk drink with sesame seed flour - Baroro, Geb Roj; Carlos, Christine Ann; Peña, Emmanuel Johann III; Reyes, Justine Aethelberht (College of Engineering, University of the Philippines Diliman, 2014)
This study provides the assessment of the feasibility of commercializing Cerealusog, a cereal milk drink enriched with iron and calcium through the use of sesame seeds, targeting children aged 4-9 years old, with the goal of providing a more nutritious snack or breakfast alternative. For the first part of the study, the proponents focused on defining the product and its characteristics. Based on the specifications of the product as presented by Cancino in her thesis, the proponents deemed that, with the prevalence of undernourishment and malnourishment in children aged 4-9 years old in socio-economic classes lower C and D, the product would be a significant step in alleviating hunger in children. From there, the proponents projected the growth of the potential market by conducting a survey and by obtaining growth rates and projection from the Philippines Statistics Authority, and were able to observe a steady growth in the chosen target market. A marketing mix was then determined which would suite the market's preferences and consumption patterns. Aside from the market feasibility, the proponents also assessed the technical feasibility of the product. From the projected growth of the market, they were to obtain the projected demand for the product over a 5-year period. Based from the demand, the proponents determined the types and quantities of machine to be used, the type of production, the number of employees, the type of transportation and distribution to employ, and other fees that would apply. Afterwards, since the aim of the company is to help alleviate hunger in children, they decided that they would partner with the Department of Education in its feeding program which would allow the company to reach a larger market. The total costs and revenues were projected based on the market and technical aspects of the product, and were then used to conduct a financial analysis. From the results of the analysis, it was deemed that the project would be feasible with a new positive gain in its fifth year. For possible further studies, the proponents would recommend that a study on the optimal period to expand the project to a larger scale be done and to determine the optimal production volumes and methods. Furthermore, the proponents would also recommend tapping into other non-profit organizations with the same goal so as to reach out to other potential markets of the product.